Promoting prosperity and stability : the EMU anchor in candidate and potential candidate countries. - European Commission : Directorate-General for Economic and Financial Affairs. (European Economy. Economic papers, 2008)
This paper analyses the euro as external anchor in the Western Balkans and their process of fiscal consolidation in the context of future EU accession.